Conservation, Compensation, and Evolution of N-Linked Glycans in the HIV-1 Group M Subtypes and Circulating Recombinant Forms. (9th December 2012) - Travers, Simon A.
Abstract : The "glycan shield" exposed on the surface of the HIV-1 gp120 env glycoprotein has been previously proposed as a novel target for anti-HIV treatments. While such targeting of these glycans provides an exciting prospect for HIV treatment, little is known about the conservation and variability of glycosylation patterns within and between the various HIV-1 group M subtypes and circulating recombinant forms. Here, we present evidence of strong strain-specific glycosylation patterns and show that the epitope for the 2G12 neutralising antibody is poorly conserved across HIV-1 group M. The unique glycosylation patterns within the HIV-1 group M subtypes and CRFs appear to explain their varying susceptibility to neutralisation by broadly cross-neutralising (BCN) antibodies. Compensatory glycosylation at linearly distant yet three-dimensionally proximal amino acid positions appears to maintain the integrity of the glycan shield while conveying resistance to neutralisation by BCN antibodies. We find that highly conserved clusters of glycosylated residues do exist on the gp120 trimer surface and suggest that these positions may provide an exciting target for the development of BCN anticarbohydrate therapies.